ChemInform Abstract: Molybdenum Phosphosulfide: An Active, Acid‐Stable, Earth‐Abundant Catalyst for the Hydrogen Evolution Reaction. Issue 13 (March 2015) - Kibsgaard, Jakob; Jaramillo, Thomas F.
Abstract Surface‐sulfur modified MoP catalyst is prepared by drop casting aliquots of 0.25 M (NH4)6Mo7O24 and (NH4)2HPO4 solutions on a Ti foil support followed by drying, thermal reduction (5% H2/N2, 650 °C, 2 h), and thermal sulfidation (10% H2S/H2, 400 °C, 15 min).